In vitro Studies on the Effect of Prosopis cineraria On the Motility and Acetylcholinesterase of Cotylophoron cotylophorum (Indo-American Journal of Life Sciences and Biotechnology, 2022)
Resulting from the paramphistome, paramphistomosis Diseases caused by the cotylophoron cotylophorumare common in ruminants kept as pets. Worm control strategies across the globe rely on chemical control ofhelminths in conjunction with better management. Nevertheless, screening medicinal plants for theiranthelmintic activity has been proposed in response to the growing issue of helminth resistance toanthelmintics. In this study, the motility and acetylcholinesterase (AChE) enzyme of Cotylophoroncotylophorum were used to evaluate the anthelmintic effectiveness of Prosopis cineraria bark. Flukes weresubjected to ethanol extract of Prosopis cineraria bark (PcEE) at doses of 1, 2, 3, 4, and 5% for 2, 4, and 8hours, respectively. We used an Electronic Micromotility Meter (EMM) to quantify the parasites' motilityresponse after they were treated with drugs. Electronic monitoring of the parasites' motility after medicationtreatment reveals that the pharmaceuticals had a direct effect on the parasites' motility. After 8 hours ofexposure to PcEE, the parasites' motility response was most inhibited at a dose of 5%. Analyzed was AChE.The activity of AChE was markedly reduced by PcEE. Because AChE is involved in neurotransmission,blocking it causes the parasite to lose its "biochemical hold-fast" and become paralyzed, making it easy toexpel from the host. When it comes to C. cotylophorum, PcEE is a great anthelmintic. With its potential forsafe and environmentally friendly usage, it might replace anthelmintic chemotherapeutic drugs. Additional invivo research are need to determine the study's practical value, nevertheless.